Cofilin-1 levels and intracellular localization are associated with melanoma prognosis in a cohort of patients - Bracalente, Candelaria (Oncotarget, 2018)
Melanoma is an aggressive cancer with highly metastatic ability. We propose cofilin-1, a key protein in the regulation of actin dynamics and migration, as a prognostic marker. We determined cofilin-1 levels in a retrospective cohort of patients with melanomas and benign lesions of melanocytes (nevi) by immunohistochemistry. Higher cofilin-1 levels were found in malignant melanoma (MM) with Breslow Index (BI)>2 vs MM with BI<2, melanoma in situ (MIS) and nevi and also in MM with metastasis vs MM without detected metastasis. Kaplan-Meier survival curves were performed, clustering patients according to either the type of melanocytic lesions or cofilin-1 level. Survival curves demonstrated worse prognosis of patients with high vs low cofilin-1 levels. TCGA database analysis of melanoma also showed low survival in patients with upregulated cofilin-1 mRNA vs patients without alteration in CFL1 mRNA expression. As cofilin-1 has a dual function depending on its intracellular localization, we evaluated nuclear and cytoplasmic levels of cofilin-1 in melanoma and nevi samples by immunofluorescence. MM with high Breslow index and metastatic cells not only presented cytoplasmic cofilin-1, but also showed this protein at the nucleus. An increase in nuclear/cytoplasmic cofilin-1 mean fluorescence ratio was observed in MM with BI>2 vs MM with BI<2, MIS and nevi. In conclusion, an association of cofilin-1 levels with malignant features and an inverse correlation with survival were demonstrated. Moreover, this study suggests that not only the higher levels of cofilin-1, but also its nuclear localization can be proposed as marker of worse outcome of patients with melanoma.